Unveiling Vertical State Downscaling: Identity and/or the Economy? - Joan Costa-i-Font (London School of Economics and Political Science (LSE), European Institute, 2010)
State rescaling may take a variety of shapes although scant research has been carried out into the mechanisms and economic incentives that underpin rescaling processes. Recent literature in economics, economic sociology and political economy has identified at least two broad rescaling mechanisms, namely the development of regional identity - operating at the cultural level and proxing preference heterogeneity-, and the heterogeneity in levels of economic development, which influence the extent of regional redistribution. This paper empirically examines the mechanisms of vertical state rescaling by drawing upon empirical evidence from Catalonia and the Basque Country, to explore the evolution of sub-state identity and the rise of inter-territorial fiscal grievances - weakening intraregional economic solidarity. Findings corroborate the idea that the combination of widening sub-national identity raises the costs of managing heterogeneous spatial identities and strengthens support for vertical state downscaling. Similarly, ending regional fiscal solidarity it is found that Catalonia would increase their income by 37%. However, the effect of regional identity exceeds that of regional redistribution in explaining state rescaling support in the magnitude of one to seven. These findings speak to the debate on the formation of Europe, in that they suggest limits to regional redistribution and pinpoint the importance of a common identity.
Keywords: 330; vertical state downscaling; spatial identity; regional elites; devolution; Basque Country and Catalonia; Europe